A static and dynamic coupling approach for maintaining ecological networks connectivity in rapid urbanization contexts. (1st October 2022) - Shen, Zhou; Wu, Wei; Chen, Shaofeng; Tian, Shiqi; Wang, Jiao; Li, Linjuan
Abstract: Ongoing, rapid urbanization accompanied by habitat fragmentation and loss poses great threats to biodiversity and the ecosystem. Maintaining ecological networks (ENs) connectivity provides a powerful landscape strategy to confront these ecological consequences. However, for rapid urbanization contexts, the connectivity of ENs cannot be well maintained by the current protection system under the impacts of continuous land expansion. Although the stepping-stones protection offers feasible connectivity-based schemes, the degree of their availability in dynamic land expansion scenarios is unclear. In this study, we developed a static and dynamic coupling approach that emphasized a comprehensive ENs protection system should be incorporated into future land expansion scenarios. The system included landscape defects identification which can be built as stepping-stones outside the traditional ENs establishment framework for ENs connectivity restoration. Taking Southern Jiangsu as the application case, our results showed that there were 127 existing landscape defects covering a total area of 285.00 km 2, in the fragmented regional ENs, constituting the group of stepping-stones that can efficiently improve the ENs connectivity. Meanwhile, we confirmed that these stepping-stones were vulnerable although they were included in the protection system, with 70% of the total would be degraded and 13% lost due to the encroachments caused by future land expansion. Therefore, we proposed an alternative scenario that designated stepping-stones as restricted land expansion areas integrated into the comprehensive ENs protection system to maintain their persistent roles in connectivity. This study highlighted the weakness of traditional ENs establishment for rapid urbanization contexts and provided practical contributions to improving the effect of regional ecological protection and restoration.